Prospects of amalgamating Indigenous Knowledge strategies with biomedical strategies in the guidance and counselling curriculum for Secondary Schools in Zimbabwe: a focus on HIV/AIDS - Hungwe, Ledwina (My University, 2021)
The HIV/AIDS epidemic has devastated many individuals, families and communities. The impact of HIV/AIDS has negatively affected teaching and learning in the education sector, over-loaded health services and negatively impacted on family food security as well as on human dignity. The global, regional and national response to HIV/AIDS is based on the biomedical human rights prevention, treatment, care and support strategies. Despite all the resources and efforts placed in the biomedical response strategies in Zimbabwe, HIV prevalence remains high. The economic crises, socio-cultural and other challenges faced by Zimbabwe and other countries in implementing biomedical strategies for HIV/AIDS management have prompted people to use Indigenous Knowledge (IK) strategies for managing HIV/AIDS. Many people in Zimbabwe use both IK strategies and biomedical strategies for HIV/AIDS management. There is a worldwide recognition of the sustainability of IK. In Zimbabwe, the Ministry of Education, Sports Arts and Culture (MOESAC), the then Ministry of Primary and Secondary Education and the National Cultural Policy, Section 2.1 (2004) emphasised that the Zimbabwean traditional knowledge and education goals should provide sources for the curriculum needs and that the knowledge should be infused in the curriculum. Yet there are no clear implementation guidelines for teachers on what IK to amalgamate in the curriculum and how to use it. My study aimed to amalgamate IK and Biomedical Knowledge strategies through the teaching and learning about HIV/AIDS in the Guidance and Counselling curriculum for secondary schools in Zimbabwe. This interpretive research study sought to explore and document IK HIV/AIDS strategies in Mazowe Gold Mine community in Zimbabwe. The study was carried out in collaboration with cultural elders in Mazowe Gold Mine Community in Zimbabwe. The Culturally Aligning Classroom Science (CACS) framework (Mpofu, 2016) was adapted and used as the conceptual framework for this study. Data were generated using padareconversational meetings, observations, interviews and document analysis under the umbrella of the Indigenous Amalgamative Methodology (IAM). The research study findings show that cultural elders are important sources of IK strategies for HIV/AIDS management. If these IK strategies are harnessed, they may contribute to the teaching and learning about HIV/AIDS in the classroom and lead to linkages between the schools or education systems, the home and the wider community in the fight against HIV/AIDS. The study findings also show that the cultural elders have valuable contributions to make to the amalgamation of IK into classroom science. The study recommends the involvement of cultural elders and other stakeholders and for government support for IK amalgamative classroom science. The study also recommends teacher capacitation in IK amalgamative research for the teaching and learning of HIV/AIDS in the classroom
A thesis submitted to the Faculty of Humanities, University of Witwatersrand, Johannesburg, in fulfilment of the requirements of the degree of Doctor of Philosophy, 2021
Keywords: HIV-positive persons-Zimbabwe; AIDS (Disease)-Zimbabwe